SENSOR MQ-2 DETEKSI ASAP ROKOK BERBASIS INTERNET OF THINGS - Umar, Nuraeni; A. K., Sahbuddin; Halide, Lidemar; Rusjdi, Maudy Imayanthi; Ijsam, Ismah Afifah (Jurnal Teknologi Elekterika, 2023)
Cigarette smoke contains toxic chemicals such as carbon monoxide (CO), nicotine and tar. The dangerous/poisonous ingredients in cigarettes cause health problems for those who smoke (active smokers) or those who don't smoke (passive smokers). To avoid the accumulation of cigarette smoke in the room, this research was created and carried out to detect cigarette smoke and reduce the levels of cigarette smoke in the room. Fan. will emit cigarette smoke into the room. The results of the detection of cigarette smoke levels will be sent to Labtop. This system was built using an MQ-2 sensor, ESP8266 microcontroller. The implementation of the cigarette smoke detection system is installed in 3 different rooms/places and is accessed by Internet of Things (IoT) network users. The research results show that every room where this system is installed will send data from cigarette smoke detection results to the lab. The MQ-2 sensor detects cigarette smoke, the data is sent to the internet network via the ESP8266, the data will be displayed on the laptop. From the sample test the tool responded well. This system will activate the fan at certain levels of cigarette smoke to reduce the level of cigarette smoke in the room. When the level is 0 ppm with the Green LED indicator on, the fan is not working or OFF. When the level shows 7 ppm the LED indicator lights up yellow and the fan will turn ON. For the red LED, the cigarette smoke level displayed is 32 ppm with the fan ON. These results prove that the system is functioning properly, detecting and controlling the operation of the fan to remove cigarette smoke from the room and transmit data to the internet network.